Contribution of farmer perception and project implementation process towards adoption of rainwater harvesting tanks for food security in Bolero, Malawi - Luhanga, Major Chimukwayaya (Mzuzu University, 2015)
This study explored the contribution of farmer perception and project implementation process to adoption of rainwater harvesting (RWH) tanks for food security in Bolero, Malawi. Data was collected from 10 purposefully selected villages using semi-structured interviews, focus group discussions and direct observations involving 68 respondents comprising key informants, extension workers, project participants and non-participants. Data collected was analysed using descriptive content analysis. Study results show that unsuitable aboveground RWH tank size was promoted for backyard irrigation. The 10m3 tanks could not irrigate crops to maturity and farmers could not realize attractive benefits from produce. Results also reveal inappropriate approach use during technology introduction. Project introduction lacked publicity and community involvement in planning and participant selection. Participant selection was biased towards village heads hence RWH tanks were perceived as meant for village heads. The study concludes that RWH tank size and implementation approach created negative community perception towards RWH tank technology and thus low adoption. To enhance technology adoption, this study recommends improvement in tank size and implementation approach. Aboveground RWH tanks with capacity 30m3and above should be promoted in arid areas under high publicity and community involvement in decision making.